Expression and Function of Different Guanine-Plus-Cytosine Content 16S rRNA Genes in Haloarcula hispanica at Different Temperatures - Sato, Yu; Fujiwara, Taketomo; Kimura, Hiroyuki (Frontiers in Microbiology, 2017)
The halophilic archaeon Haloarcula hispanica harbors three ribosomal RNA (rRNA) operons (rrnA, rrnB, and rrnC) that contain the 16S rRNA genes rrsA, rrsB, and rrsC, respectively. Although rrsB and rrsC (rrsBC) have almost identical sequences, the rrsA and rrsBC sequences differ by 5.4%, and they differ by 2.5% with respect to guanine-plus-cytosine content (PGC). The strong correlation between the typical growth temperatures of archaea and PGC of their 16S rRNA genes suggests that Har. hispanica may harbor different 16S rRNA genes having different PGC to maintain rapid growth in a wide range of temperatures. We therefore performed reverse transcription–coupled quantitative PCR to assess expression levels of rrsA (PGC, 58.9%) and rrsBC (PGC, 56.4–56.5%) at various temperatures. The expression ratio of rrsA to rrsBC increased with culture temperature. Mutants with complete deletions of one or two of the three rRNA operons were constructed and their growth rates at different temperatures compared to that of the wild-type. The growth characteristics of the rRNA operon single-mutant strains were indistinguishable from the wild-type. The rRNA operon double-mutant strains maintained the same temperature range as wild-type but displayed reduced growth rates. In particular, the double-mutant strains grew much slower than wild-type at low temperature related to minimum growth temperature of the wild-type. On the other hand, at physiologically high temperatures the wild-type and the double-mutant strain which harbors only rrnA with high-PGC rrsA grew significantly faster than the double-mutant strain which harbors only rrnC with low-PGC rrsC. These findings suggest the importance of 16S rRNAs transcribed from rrsA with high PGC in maintaining rapid growth of this halophilic archaeon at raised growth temperatures.